An efficient metal- and solvent-free organocatalytic system for chemical fixation of CO2 into cyclic carbonates under mild conditions. Issue 5 (21st December 2015) - Wang, Lin; Zhang, Guangyou; Kodama, Koichi; Hirose, Takuji
Abstract : An efficient organocatalytic system was developed for the synthesis of cyclic carbonates from epoxides and CO2 (25–45 °C, 1 atm) in high-to-excellent yields (85–97%). Moreover, the 2, 6-pyridinedimethanol system could be recycled several times without significant loss of activity. Abstract : An efficient, metal- and solvent-free catalytic system was developed for the conversion of CO2 and epoxides to the corresponding cyclic carbonates under mild conditions ( T = 25–45 °C, 1 atm CO2 ) in high-to-excellent yields. The catalyst could be easily recycled, providing a more sustainable process for the chemical fixation of CO2 .